A Bayesian model for integrating multiple sources of lifetime information in system reliability assessments. - Reese, C. Shane
We present a Bayesian model for assessing the reliability of multicomponent systems. Novel features of this model are the natural manner in which lifetime data collected at either the component, subsystem or system level are integrated with prior information at any level. The model allows pooling of information between similar components, the incorporation of expert opinion, and straightforward handling of censored data. The methodology is illustrated with two examples.
Keywords: Censored data; Expert opinion; Lifetime data; Markov chain monte carlo; Multicomponent system; Multilevel data; Prior information